Popotnice skozi mračne pokrajine - poporodne stiske v vsakdanjem življenju mladih mater - Drglin, Zalka (Socialna pedagogika (Ljubljana), 2006)
The article presents dominant concepts about postnatal mental problems and looks beyond too-narrow scientific arguments about them. The main question about everyday practices of motherhood isČ are we talking about power relationships or are they the a way to freedomŽ We have to think about complexity of this problem and in the same time about individual choices. By organizing self-help groups and support groups for women, a telephone line called "mamaZOFA", individual consultations and crises team there is a new start for specific community life in Slovenia. A critical stance needs to be developed about the prescribed way to be "good mother" - as this in the same time enables an extension of forms of support to women.
Keywords: female; ženska; rojstvo; birth; mental health; duševno zdravje; matere; svetovanje; woman; ženske; childbirth; porod; mentalno zdravje